Acute hyperglycaemia affects anorectal motor and sensory function in normal subjects. Issue 4 (1st October 1997) - Russo, A; Sun, W M; Sattawatthamrong, Y; Fraser, R; Horowitz, M; Andrews, J M; Read, N W
Abstract : Background —The pathogenesis of anorectal dysfunction, which occurs frequently in patients with diabetes mellitus, is poorly defined. Recent studies indicate that changes in the blood glucose concentration have a major reversible effect on gastrointestinal motor function. Aims —To determine the effects of physiological changes in blood glucose and hyperglycaemia on anorectal motor and sensory function in normal subjects. Subjects —In eight normal subjects measurements of anorectal motility and sensation were performed on separate days while blood glucose concentrations were stabilised at 4, 8, and 12 mmol/l. Methods —Anorectal motor and sensory function was measured using a sleeve/sidehole catheter incorporating a balloon, and electromyography. Results —The number of spontaneous anal relaxations was greater at 12 mmol/l than at 8 and 4 mmol/l glucose (p<0.05 for both). Anal squeeze pressures were less at a blood glucose of 12 mmol/l when compared with 8 and 4 mmol/l (p<0.05 for both). During rectal distension, residual anal pressures were not significantly different between the three blood glucose concentrations. Rectal compliance was greater (p<0.05) at a blood glucose of 12 mmol/l when compared with 4 mmol/l. The threshold volume for initial perception of rectal distension was less at 12 mmol/l when compared with 4 mmol/l (40 (20–100) ml versus 10 (10–150) ml, p<0.05). Conclusions —An acute elevation of blood glucose to 12 mmol/l inhibits internal and external anal sphincter function and increases rectal sensitivity in normal subjects. In contrast, physiological changes in blood glucose do not have a significant effect on anorectal motor and sensory function.